2-Fluoro-5-nitrophenyldiazonium: A Novel Sanger-Type Reagent for the Versatile Functionalization of Alcohols - Fischer, Oliver; Heinrich, Markus (Chemistry - A European Journal, 2021)
As a novel Sanger-type reagent, 2-fluoro-5-nitrophenyldiazonium tetrafluoroborate enabled the versatile functionalization of primary and secondary aliphatic alcohols. Based on a mild nucleophilic aromatic substitution of the fluorine atom under unprecedented, base-free conditions, the diazonium unit on the aromatic core of the resulting aryl-alkyl ether could be employed for such diverse transformations as radical C−H activation and cyclization, as well as palladium catalyzed cross-coupling reactions.
CRIS-Team Scopus Importer:2021-03-05
Keywords: C−C bond formation; C−H activation; diazonium; nucleophilic aromatic substitution; Sanger reagent